Pelatihan penerapan assessment as, for, of learning berbantuan gamifikasi di Sekolah Menengah Pertama Negeri Kabupaten Garut - Enung Nurhayati; Wikanengsih Wikanengsih (IKIP SILIWANGI, 2023)
This commitment in the form of training is motivated by the professional competence of teachers in the development of learning assessments. The assessment functions as a teacher's effort to be able to find the advantages and disadvantages of the learning process that is being implemented or that has been implemented. However, there are still many teachers who consider the assessment process to be only a formality. The assessment is not authentic, or the teacher gives conventional assessments, which tend to be carried out only to measure graduate learning outcomes, as if the assessment were separate from the learning process, without paying attention to assessments that can improve student competency during the learning process. Under these conditions, teachers need an assessment approach that is used in learning. This training aims to train teachers in developing an assessment of learning (AafoL) model through a gamification-assisted genre pedagogy approach. The training was held at the MGMP Indonesian Middle School, Garut Regency, West Java, at SMPN 2 Cibiuk, Garut Regency. The training uses methods: tutorial, workshops, structured assignments, and consultations. As a result, the teacher can have a basic understanding of assessment and its application in learning Indonesian. The teacher can compose HOTS-based Indonesian questions and provide good assessments.